2013
DOI: 10.1682/jrrd.2013.02.0035
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to high-level mobility in male servicemembers with traumatic lower-limb loss

Abstract: The purpose of this study was to examine the possible relationship between factors modifiable by rehabilitation interventions (rehabilitation factors), other factors related to lower-limb loss (other factors), and high-level mobility as measured by the Comprehensive High-Level Activity Mobility Predictor (CHAMP) in servicemembers (SMs) with traumatic lower-limb loss. One-hundred eighteen male SMs with either unilateral transtibial amputation (TTA), unilateral transfemoral amputation (TFA), or bilateral lower-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The cohort of amputees reported in this study had a mean NISS of 40AE15, which we believe constitutes the highest severity of traumatic amputee injury in the available literature. 11,12 Despite this, upon completion of a comprehensive and intensive rehabilitation pathway, these patients had functional and mental health status comparable with that of the general population. Patient mobility is a critical component of successful rehabilitation and vital in aiding ADL.…”
Section: Discussionmentioning
confidence: 95%
“…The cohort of amputees reported in this study had a mean NISS of 40AE15, which we believe constitutes the highest severity of traumatic amputee injury in the available literature. 11,12 Despite this, upon completion of a comprehensive and intensive rehabilitation pathway, these patients had functional and mental health status comparable with that of the general population. Patient mobility is a critical component of successful rehabilitation and vital in aiding ADL.…”
Section: Discussionmentioning
confidence: 95%
“…Hamamura et al reported, in a high quality study, no significant difference between the successful and unsuccessful ambulator groups when considering amputation level (17). Guanard et al., in a high quality article, reported on the importance of an intact knee joint for providing the TTA patient with the ability to return to high-level mobility activities following rehabilitation (31). Stineman et al reported ADLs and mobility (physical functioning) using gains in motor FIM™ scores achieved by rehabilitation discharge.…”
Section: Discussionmentioning
confidence: 99%
“…van Eijk et al, in a medium quality article, reported that functional ambulation (Functional Ambulation Catagories (FAC) score, which measures the independency of gait) was significantly positively associated with prosthetic use (20). Guanard et al, in a high quality article, reported rehabilitation-related factors, such as lower limb strength, standing and dynamic balance, and ability to displace the center of mass over the base of support, were all significantly related to ability to perform high-level mobility activities (31.) Sansam et al previously reported that two medium to high quality studies with the same first author have looked at physical fitness and its relationship to walking ability following unilateral above knee amputation.…”
Section: Discussionmentioning
confidence: 99%
“…There has been recent literature that has supported this (Gaunaurd et al, 2013;Knezevic et al, 2016;Stineman et al, 2010;van Eijk et al, 2012;Webster et al, 2012), and literature that has refuted this assumption (Czierniecki, Turner, Williams, Hakimi, & Norvell, 2012;Gremeaux et al, 2012;Suckow et al, 2012). Notably, the impact of advanced knee joint technology on walking ability was only reported in one of these publications (Gaunaurd et al, 2013) while older publications preceded the commercialization of MPKs. Fortington et al (Fortington et al, 2012) recently noted "poorer performance by people with a transfemoral amputation versus a transtibial level was apparent where compared".…”
Section: Discussionmentioning
confidence: 96%